2016
DOI: 10.1176/appi.ps.201500311
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Personal Medicine as Part of Self-Directed Care: Expanding Perspectives on Medical Necessity

Abstract: Individuals with serious mental illness identified personal-medicine strategies to address needs that are currently unmet by traditional mental health services. Self-directed care may be a service delivery option that allows consumers to access their own personal medicine and better address their needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
4
21
0
Order By: Relevance
“…Descriptive analysis of nontraditional purchases revealed that the most common were for needs related to transportation, communication, medical expenses, housing, and health and wellness. These findings were surprisingly consistent with those from the study of a mental health self-directed care program in Pennsylvania, in which the most common nontraditional expenditures were related to transportation, maintaining health, diet and fitness, and handling stress (51), and with those from a study of a mental health self-directed care program in Florida, in which the most common nontraditional expenditures were in the categories of fitness, wellness, medical needs, transportation, and self-help (15). As others have noted, the consistency of these nontraditional purchases suggests that services and supports available from the traditional mental health system are inadequate to meet consumer needs (16).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Descriptive analysis of nontraditional purchases revealed that the most common were for needs related to transportation, communication, medical expenses, housing, and health and wellness. These findings were surprisingly consistent with those from the study of a mental health self-directed care program in Pennsylvania, in which the most common nontraditional expenditures were related to transportation, maintaining health, diet and fitness, and handling stress (51), and with those from a study of a mental health self-directed care program in Florida, in which the most common nontraditional expenditures were in the categories of fitness, wellness, medical needs, transportation, and self-help (15). As others have noted, the consistency of these nontraditional purchases suggests that services and supports available from the traditional mental health system are inadequate to meet consumer needs (16).…”
Section: Discussionsupporting
confidence: 84%
“…As others have noted, the consistency of these nontraditional purchases suggests that services and supports available from the traditional mental health system are inadequate to meet consumer needs (16). These results also suggest that participants have insight into what would best support their recovery and that enhancing their range of choices facilitates the development of the personal medicine necessary to enhance their own mental health (51).…”
Section: Discussionmentioning
confidence: 72%
“…Statistics showed that the average length of hospital stay in the United States is 6.9 days/person, Australia is 7.4 days/person, and Ireland is 9.0 days/person while the average length of hospital stay for Grade-A tertiary hospital of China is 13.5 days/person. [ 9 ] Researches also showed that the excessive length of hospital stay is not entirely due to the needs of clinical diagnosis and treatment. Moreover, the phenomenon might be a large extent, results from defects of the medical management control, and low work efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…community in a manner similar to everyone else. There is ample evidence suggesting that community participation is a medical necessity itself, having a positive impact on the physical, cognitive, and mental health of individuals with serious mental illnesses (11,12). Physical health issues are associated with limited energy and pain, which could reduce enthusiasm for participation and lead to diminished stamina.…”
mentioning
confidence: 99%